The business confidence in the manufacturing industry: a panel analysis - Potrich, Ani Caroline Grigion; Vieira, Kelmara Mendes; Filho, Pascoal José Marion; Fraga, Luana Santos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Investment decisions are permeated with uncertainties that are often derived from the future expectations of change. In this context and guided by the fact that the Industrial Confidence Index has shown decline, particularly among entrepreneurs in the manufacturing industry, it is important to analyze the behavior of the index over the past years. Therefore, the present study aims to search to find what the impact of macroeconomic variables have the Industrial Confidence Index. We used an econometric model of panel data with random effects. The main results suggest that the positive change of the index compared to the previous month, as well as positive variation of the real revenues of the previous month and the previous two months, impacting positively in the index. However, it was established that the positive change in the value of the US Dollar and inflation in the previous month, there is a decrease in the index. Changes in the index itself in the period, followed by the dollar, have a greater impact on the Business Confidence Index. These results demonstrate that the future expectations about the behavior of macroeconomic variables is crucial for estimating the cost of capital and the estimates of revenues and costs.